Sistem Kontrol Pendidikan Karakter di Sekolah dan Keluarga - Imam Mushafak (Institut Agama Islam Negeri (IAIN) Tulungagung, 2015)
So far, the movement of character building in educational institutions is not yet effective. It can be seen that students schools do not behave well as represented by the occurrence of juvenile delinquency in various forms which even against the law. There must be a collaboration between school and parent as to support the implementation of character education. Family is the basis for developing students’ good character.